A reliable and timely medium access control protocol for vehicular ad hoc networks. (29th March 2013) - Rezazade, Lida; Aghdasi, Hadi S.; Ghorashi, Seyed Ali; Abbaspour, Maghsoud
Many vehicular safety applications can be implemented more easily and practically by using reliable and real–time communications between vehicles and roadside infrastructures. Neither schedule–based nor contention–based conventional MAC protocols can properly satisfy the safety requirements of such applications. In contention–based protocols, packets may experience unbounded delays and schedule–based protocols are sensitive to users' motion. In this paper, a new STDMA MAC protocol which provides both reliable and real–time medium access is introduced. Simulation results show that the proposed protocol has succeeded in providing an acceptable level of reliable and real–time communications, simultaneously.